Práticas educativas de introdução a agroecologia nas escolas itinerantes do campo no Paraná - Leite, Valter de Jesus; Conceição, Luiz Arthur (Ambiente & Educação: Revista de Educação Ambiental, 2020)
Objetivamos pelo presente estudo abordar a Educação do Campo na interface com a agroecologia, situada no trabalho educativo das Escolas Itinerante presentes em ocupações de terra do MST no Paraná. Metodologicamente, recorremos a uma abordagem qualitativa por meio de pesquisa documental, bibliográfica e de campo. Tecemos reflexões acerca das aproximações conceituais entre a Educação do Campo e a Educação Ambiental. A partir da análise de três práticas educativas de introdução à agroecologia, reafirmamos lições projetivas coletivas que contribuem na incorporação da agroecologia e de dimensões socioambientais no trabalho educativo das escolas do campo vinculada a luta pela transformação das condições de vida no campo, ao mesmo tempo que acessam os conhecimentos acumulados pela humanidade.The inclusion of agroecology educative practices in the itinerary rural schools in ParanaThe objective of the present study is to approach Rural Education at the interface with agroecology, located in the educational work of the Itinerant Schools present in land occupations of the MST in Paraná. Methodologically, we resort to a qualitative approach through documentary, bibliographic and field research. We made reflections about the conceptual approximations between Rural Education and Environmental Education. From the analysis of three educational practices of introduction to agroecology, we reaffirm collective projective lessons that contribute to the incorporation of agroecology and socioenvironmental dimensions in the educational work of rural schools linked to the struggle for the transformation of life conditions in the countryside, at the same time that access the knowledge accumulated by humanity. Keywords: Rural Education. Agroecology. Environmental Education. Pedagogic Practices. Human Development.